A Toxicological Evaluation of a Standardized Hydrogenated Extract of Curcumin (CuroWhite™) - Alastimmanahalli Narasimhiah Ravikumar; Joby Jacob; Sreeraj Gopi; Tumkur Subbarao Jagannath (Journal of Toxicology)
A series of toxicological investigations were conducted in order to evaluate the genotoxic potential and repeated-dose oral toxicity of CuroWhite, a proprietary extract of curcumin that has been hydrogenated and standardized to not less than 25% hydrogenated curcuminoid content. All tests were conducted in general accordance with internationally accepted standards. The test item was not mutagenic in the bacterial reverse mutation test or in vitro mammalian chromosomal aberration test, and no in vivo genotoxic activity was observed in rat bone marrow in the micronucleus test. A 90-day repeated-dose study was conducted in male and female Sprague-Dawley rats. Two mortalities occurred in the main and satellite high-dose groups and were determined due to gavage error. No organ specific or other toxic effects of the test item were observed up to the maximum dose of 800 mg/kg bw/day, administered by gavage. NOAEL was, therefore, estimated as 800 mg/kg bw/day.